Analytical methods based on the light-scattering of plasmonic nanoparticles at the single particle level with dark-field microscopy imaging. Issue 2 (5th December 2016) - Li, Tian; Wu, Xi; Liu, Feng; Li, Na
Abstract : This minireview summarizes analytical methods based on the light-scattering of gold nanoparticles with the dark-field microscopy imaging technique at the single particle level. Abstract : This minireview summarizes analytical methods based on the light-scattering of plasmonic nanoparticles, primarily gold nanoparticles (AuNPs), at the single particle level from recent year publications. Examples are presented to illustrate simple and highly sensitive approaches based on AuNP localized surface plasmon resonance light-scattering with the dark-field microscopy imaging technology.